Resistance Toward Chlorhexidine in Oral Bacteria – Is There Cause for Concern? - Cieplik, Fabian; Jakubovics, Nicholas S.; Buchalla, Wolfgang; Maisch, Tim; Hellwig, Elmar; Al-Ahmad, Ali (Frontiers in Microbiology, 2019)
The threat of antibiotic resistance has attracted strong interest during the last two decades, thus stimulating stewardship programs and research on alternative antimicrobial therapies. Conversely, much less attention has been given to the directly related problem of resistance towards antiseptics and biocides. While bacterial resistances towards triclosan or quaternary ammonium compounds have been considered in this context, the bis-biguanide chlorhexidine (CHX) has been put into focus only very recently when its use was associated with emergence of stable resistance to the last-resort antibiotic colistin. The antimicrobial effect of CHX is based on damaging the bacterial cytoplasmic membrane and subsequent leakage of cytoplasmic material. Consequently, mechanisms conferring resistance towards CHX include multidrug efflux pumps and cell membrane changes. For instance, in staphylococci it has been shown that plasmid-borne qac (‘quarternary ammonium compound’) genes encode Qac efflux proteins that recognize cationic antiseptics as substrates. In Pseudomonas stutzeri, changes in the outer membrane protein and lipopolysaccharide profiles have been implicated in CHX resistance. However, little is known about the risk of resistance towards CHX in oral bacteria and potential mechanisms conferring this resistance or even cross-resistances towards antibiotics. Interestingly, there is also little awareness about the risk of CHX resistance in the dental community even though CHX has been widely used in dental practice as the gold-standard antiseptic for more than 40 years and is also included in a wide range of oral care consumer products. This review provides an overview of general resistance mechanisms towards CHX and the evidence for CHX resistance in oral bacteria. Furthermore, this work aims to raise awareness among the dental community about the risk of resistance towards CHX and accompanying cross-resistance to antibiotics. We propose new research directions related to the effects of CHX on bacteria in oral biofilms.